0 Members and 1 Guest are viewing this topic.

KE+PE=CWhere KE is for the kinetic energy, and PE if for potential energy, and C is some constant. This constant is defined as (Mgh) which is also a mathematical expression, which states that mass multiplied by gravity and multiplied by height, yields the kinetic energy added with the potential energy. So if C=Mgh, then we can rearrange the above equation:KE+PE=Mgh

QuoteKE+PE=CWhere KE is for the kinetic energy, and PE if for potential energy, and C is some constant. This constant is defined as (Mgh) which is also a mathematical expression, which states that mass multiplied by gravity and multiplied by height, yields the kinetic energy added with the potential energy. So if C=Mgh, then we can rearrange the above equation:KE+PE=MghWhat?? mgh is a formula not a constant, and why do you say KE+PE=Mgh? It's just PE=mgh.

so if PE + KE = mgh, then

Quoteso if PE + KE = mgh, then But it doesn't; it equals the total energy of the object: =PE + KE .If / when it hits the ground, its PE will be zero and its KE will have increased by the amount of PE it started with.KE(final) = PE(initial) + KE(initial)For an object in orbit (elliptical, in the general case), the total energy remains the same. It goes faster when it is nearer and slower when further away.

-h/2=v’² - v²/-2g

It is a changing length from the ground where v=0. I give up. Simply this is the way we where shown to calculate a distance from the ground.